2007
DOI: 10.1007/s00253-007-0898-8
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial and immunostimulative effect of chitosan-oligosaccharides against infection by Staphylococcus aureus isolated from bovine mastitis

Abstract: Based on our previous study evaluating the in vivo cure efficacy of chitosan on bovine mastitis, a more water-soluble chitosan-oligosaccharide (OCHT) with a high degree of deacetylation and low molecular weight was prepared to obtain high antibiotic efficacy. The growth of Staphylococcus aureus isolated from bovine mastitis was inhibited within 10 min of treatment with OCHT in concentrations ranging from 0.0001 to 0.5%. Additionally, electron microscopic observation indicated that the surface of the OCHT-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 42 publications
1
47
1
2
Order By: Relevance
“…Staphylococcus aureus by the intra-peritoneal route resulted in a higher survival rate compared with that of controls 12 .…”
Section: Introductionmentioning
confidence: 80%
“…Staphylococcus aureus by the intra-peritoneal route resulted in a higher survival rate compared with that of controls 12 .…”
Section: Introductionmentioning
confidence: 80%
“…Chitosan is a natural alkaline polysaccharide with positive charges, and also one of the most abundant natural polymers [5]- [7]. As a nontoxic, biodegradable carbohydrate polymer [8] it contains amino and hydroxyl groups per residue [9] which gives chitosan many biological activities, such as haemostatic [10], anti-inflammatory [11], antitumor activity [12] [13], antimicrobial activity [15], hypoglycemic and hypo cholesterolemic activity [16] [17] and an immune-stimulatory effect [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is the deacetylated derivative of chitin, and previous works revealed that chitosan plays a role in immune responses for plant and animal cells (Porporatto, Bianco, & Correa, 2005;Villiers et al, 2009). Chitosan oligosaccharide (Chitooligosaccharides, COS), derived from chitosan by enzymatic hydrolysis (Zhang, Du, Yu, Mitsutomi, & Aiba, 1999), is a new kind of biofunctional material which exhibits improved biological activities when compared with chitosan (Cho et al, 2008;Moon et al, 2007;Nam, Kim & Shon, 2007;PalmaGuerrero, Jansson, Salinas, & Lopez-Llorca, 2008;Rahman et al, 2008;Yoon, Moon, Park, Im, & Kim, 2007), such as inhibiting growth of bacteria and fungi, exerting anti-tumor activity, and acting as immunopotentiating effectors.…”
Section: Introductionmentioning
confidence: 99%